Teachers' perceptions of integrating virtual reality applications in English language teaching within the digital culture context - Mohammad Noor Zuhri; Ahmad Lizamuddin (Universitas Islam Sultan Agung, 2026)
The growing use of immersive technologies in language education has intensified interest in how teachers evaluate their pedagogical value and feasibility. Although previous research has documented the potential of Virtual Reality (VR) for language learning, less is known about how teachers interpret its classroom use in relation to institutional digital conditions. This descriptive qualitative study explored the perceptions and experiences of five English teachers who had prior exposure to VR-supported activities. Data were generated through semi-structured interviews and limited classroom observations and were analyzed thematically. The teachers described VR as offering immersive and contextual opportunities for language practice and perceived that some learners participated more readily during VR-supported activities. They also reported constraints related to device access, connectivity, preparation time, curriculum alignment, professional learning, and uneven institutional support. The findings indicate that teachers' experiences of VR were shaped not only by perceived pedagogical affordances but also by the resources, norms, and support available in their institutions. Because student competence, motivation, and anxiety were not directly measured, these findings should be interpreted as teacher perceptions supported by limited observational indications. The study contributes a context-sensitive account of the conditions teachers considered when using VR in English language teaching and highlights the need for pedagogically aligned materials, professional development, and realistic institutional planning.